(untitled) (Journal of Biomedical Investigation, 2015)
This is a comparative study of the mean height and weight of pre-primary children aged 3 - 5 in rural and urban communities in Anambra State with the WHO/NCHS standard. Two objectives and one hypothesis were formulated in order to determine the mean measurements of weight and height of preschool children aged 3 - 5 in the urban and rural communities of Anambra State. A cross sectional survey research design was used for the study to collect sampled data of 1280 pre-primary children from three education zones in Anambra State. These data were organized and tested with inferential statistics of t-Test. The weights and heights were compared using graphs. The results showed that pre-primary children aged 3 - 5 in the urban areas indicated higher weights and heights than those in the rural areas. These pre-primary children aged 3- 5 in both urban and rural locations had weights and heights that are higher than that of WHO/NCHS standards for their age. Based on the findings of the study, the researchers recommended that, it is important that the weight and height measurements of pre-primary children be routinely monitored as part of the school health programme.